2019
DOI: 10.1007/jhep03(2019)150
|View full text |Cite
|
Sign up to set email alerts
|

Weakly coupled de Sitter vacua with fluxes and the swampland

Abstract: It was recently argued that the swampland distance conjecture rules out dS vacua at parametrically large field distances. We point out that this conclusion can in principle be avoided in the presence of large fluxes that are not bounded by a tadpole cancellation condition. We then study this possibility in the concrete setting of classical type IIA flux compactifications with (anti-)O6-planes, (anti-)D6-branes and/or KK monopoles and show that, nonetheless, parametrically controlled dS vacua are strongly const… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 140 publications
10
75
0
Order By: Relevance
“…Despite being rare, a few classical de Sitter solutions have been found in 10d type IIA supergravity on 6d group manifolds, with O 6 orientifolds and various orbifolds; all of them are unstable. Stringy consistency issues for all these solutions have however been pointed‐out in []; this appears in agreement with the idea that no de Sitter solution could be found in a parametrically controlled regime of string theory . In particular, a difficulty was to get at the same time a large vol, a small gs, and a small number of O 6 .…”
Section: Testing the New Conjecturesupporting
confidence: 77%
“…Despite being rare, a few classical de Sitter solutions have been found in 10d type IIA supergravity on 6d group manifolds, with O 6 orientifolds and various orbifolds; all of them are unstable. Stringy consistency issues for all these solutions have however been pointed‐out in []; this appears in agreement with the idea that no de Sitter solution could be found in a parametrically controlled regime of string theory . In particular, a difficulty was to get at the same time a large vol, a small gs, and a small number of O 6 .…”
Section: Testing the New Conjecturesupporting
confidence: 77%
“…Nevertheless, the tools developed allowed us to obtain further existence constraints in , and another suggestion for the tachyon. Conjecture : we first showed, for p=4,5,6, that this conjecture would hold unless the compact manifold admits a hierarchy such that false|scriptR6false|×L21, where L is an average internal length . We were not able to exclude the possibility of such an internal hierarchy in a classical de Sitter solution, despite interesting arguments of [], and detailed information from the Einstein equation seemed needed to that end. Interestingly, we showed that having this hierarchy would lead to a scale separation with 4d.…”
Section: Results Summarymentioning
confidence: 95%
“…This idea was recently put forward in [] when analysing known classical de Sitter solutions of type IIA supergravity: those appeared inconsistent with a stringy origin, because of these extra requirements. This question was then studied formally and exemplified for p=6 in []: the conclusions turned out consistent with conjecture , without being fully general. We investigate this question here for p=4,5,6 in a 10d approach and argue that one cannot conclude on a proof of conjecture with the tools developed so far.…”
Section: Conjecture 3: No Supergravity Solution With String Originmentioning
confidence: 91%
See 2 more Smart Citations